2020
DOI: 10.31224/osf.io/qghn8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cyber-secure Framework for Power Grids Based on Federated Learning

Abstract: Cyber security is important of power grids to ensure secure and reliable power supply. This paper presented a cyber- secure framework for power grids based on federated learning. In this framework, each entity, which may be a distribution/transmission/generation service provider or even a customer, can contribute to the overall system immunity and robustness to cyber-attacks, while not required to share local data, which may have privacy, legal and property concerns. The main idea is to use the federated learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…FL is a diversely implemented architecture for optimizing the power grid system for pragmatic energy usage [7,8] via collaboration with geographically dispersed AI models. Diverse studies were suggested to design a cost-effective structure in such an energy-grid system, analyzing the challenges and issues from multiple perspectives, such as resource allocation, convergence analysis [3,4], and network cost [9].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…FL is a diversely implemented architecture for optimizing the power grid system for pragmatic energy usage [7,8] via collaboration with geographically dispersed AI models. Diverse studies were suggested to design a cost-effective structure in such an energy-grid system, analyzing the challenges and issues from multiple perspectives, such as resource allocation, convergence analysis [3,4], and network cost [9].…”
Section: Related Workmentioning
confidence: 99%
“…Depending on the environmental characteristic, D ∪ ∀j y (∃i,j) may have unique distribution, such as y i ∼ N µ(y ∀i ), σ 2 (y ∀i ) , y i ∼ Gamma(α, β), etc., and when σ ∪ ∀i D ∪ ∀j y (∃i,j) ≈ 0, the most frequent D ∪ ∀j y (∃i,j) becomes the ground truth. The left term in Case C shows the time-dependent distribution difference δ(y i , y i ) in (7). On the other hand, Case B does not consider the time-series attribute, which may incur the risk of unstable convergence while training the local models.…”
Section: Non-iid Cases With a Structural Viewmentioning
confidence: 99%
“…Al-Saffar and Musilek [84,85] used deep reinforcement learning to solve the optimal power flow (OPF) problem while considering the microgrids as agents. Federated learning has also been used for increasing cybersecurity [86] and customer privacy [87] in non-intrusive load monitoring (NILM). A summary of the discussed distributed learning applications in power systems is given in Table 2.…”
Section: Other Applicationsmentioning
confidence: 99%